Analisis Daya Saing Komoditi Unggulan Gorontalo Dalam Mendukung Ibu Kota Negara Baru Republik Indonesia - Non Endey; I Kadek Satria Arsana; Andi Yusuf Katili; Ansar Sahabi; Mohammad Abubakar Talalu (Equilibrium: Jurnal Pendidikan, 2022)
Abstract. This study aims to identify and analyze the Competitiveness of Gorontalo's Leading Commodities in Supporting the New Capital City of the Republic of Indonesia. This type of research uses a quantitative research approach with descriptive type. Sources of data in this study came from secondary and primary data. The year analyzed in this study is from 2017 to 2020. The analytical tools used in this study include; 1) Location Quotient (LQ) and Dynamic Location Quotient (DLQ) analysis, used to identify and analyze basic and prospective sectors in Gorontalo Province, 2) Shift-Share, used to analyze changes and shifts in the economic structure of Gorontalo Province, 3) Revealed Comparative Advantage (RCA), is used to identify and analyze the competitiveness of the leading export commodities of Gorontalo Province. The results showed that the basic sector in Gorontalo Province amounted to seven sectors and the identified prospective sectors were 8 sectors. Based on the combined results of the LQ and DLQ, there are two sectors that are included in the prospective basis sector, namely the Agriculture, Forestry and Fisheries sector and the Education Services sector. For changes and shifts in the economic structure of Gorontalo Province during the research year, the economic structure of Gorontalo Province is still dominated by the primary sector. The competitiveness of the leading export commodities of Gorontalo Province in 2017-2020 identified five commodities that have strong enough competitiveness that are ready to support the new IKN of the Republic of Indonesia.Keywords : Commodity, Leading Sector, Competitiveness, LQ, DLQ, Shift-Share, RCA.Abstrak. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis Daya Saing Komoditi Unggulan Gorontalo Dalam Mendukung Ibu Kota Negara (IKN) Baru Republik Indonesia. Jenis penelitian ini menggunakan pendekatan penelitian kuantitatif dengan jenis deskriptif. Sumber data penelitian ini berasal dari data sekunder dan primer. Tahun yang dianalisis pada penelitian ini mulai tahun 2017 hingga tahun 2020. Alat analisis yang digunakan pada penelitian ini antara lain; 1) analisis Location Quotient (LQ) dan Dynamic Location Quotient (DLQ), digunakan untuk mengidentifikasi dan menganalisis sektor basis dan prospektif di Provinsi Gorontalo, 2) Shift-Share, digunakan untuk menganalisis perubahan dan pergeseran struktur perekonomian Provinsi Gorontalo, 3) Revealed Comparative Advantage (RCA), digunakan untuk mengidentifikasi dan menganalisis daya saing komoditi unggulan ekspor Provinsi Gorontalo. Hasil penelitian menunjukkan bahwa sektor basis di Provinsi Gorontalo berjumlah tujuh sektor dan yang teridentifikasi sektor prospektif berjumlah 8 sektor. Berdasarkan gabungan hasil LQ dan DLQ, terdapat dua sektor yang termasuk dalam sektor basis prospektif, yaitu sektor Pertanian, Kehutanan, dan Perikanan dan sektor Jasa Pendidikan. Untuk perubahan dan pergeseran struktur ekonomi Provinsi Gorontalo belum terjadi selama tahun penelitian, struktur ekonomi Provinsi Gorontalo masih didominasi oleh sektor primer. Daya saing komoditi unggulan ekspor Provinsi Gorontalo tahun 2017-2020 teridentifikasi sejumlah lima komoditi yang memiliki daya saing cukup kuat yang siap untuk medukung IKN yang baru Republik Indonesia.Kata Kunci : Komoditi, Sektor Unggulan, Daya Saing, LQ, DLQ, Shift- Share, RCA.